VD_FINDINFO Jug / 2022 / 130 vom 30. März 2022 - VD Tribunal cantonal (2022)
REJET DE LA DEMANDE, DEMANDE ADRESSÉE À L'AUTORITÉ, RÉCUSATION, RÉVISIONDÉCISION, DÉCISION D'IRRECEVABILITÉ | 56 CPP (CH), 59 CPP (CH)